Preparation of MoS2/graphene nanostructures and their supercapacitor and hydrogen evolution reaction (HER) performances. (4th December 2019) - Mammoottil Abraham, Akhil; Bharath, G; Hai, , Abdul; Banat, Fawzi
Abstract: Herein, a simple and facile two-step sonication method was developed for the preparation of nanosheets-like MoS2 wrapped graphene nanohybrids for energy storage and hydrogen evolution reaction (HER) applications. TEM and HR-TEM images revealed that the 120 nm sized lateral diameter of sheet-like MoS2 was completely immobilized on the surfaces of graphene via the probe sonication method. The resultant nanohybrid exhibited bifunctional activities of supercapacitor and HER. With this tailored bifunctional nanoarchitecture, the nanohybrid based electrode showed an improved specific capacitance of 350 F g −1 for a current load of 1 A g −1 with a cyclic efficiency of 85 % in 6 M KOH electrolyte solution. Additionally, the developed MG11 nanohybrid was tested as an electrocatalyst for HER. The latter exhibited a low onset potential of ~125 mV with a Tafel slope of 41 mV/decade. Thus, MG11 nanohybrid presents an excellent prospect for a low-cost electrode for a supercapacitor and an electrocatalyst for hydrogen evolution reaction.